A critical thought on zakat in Islamic economic perspective - Dadang Irsyamuddin; Soritua Ahmad Ramdani Harahap; Muhammad Ulul Azmi; Syamsuri Syamsuri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2021)
This study attempted to draw critical thought on the concept of zakat through an Islamic theoretical perspective. The paper stated potential income of zakat will build up the empowered capacity as run on the assured functional way. the Mandatory donor, the rightful categories recipients, the government, and the Muslim scholars have enormous deals to elaborate hand by hand in zakat operation. Meanwhile, economic growth and empowerment are hopefully raised among public share and welfare as well. Finally, the critical thoughts take apart to reduce a classical problem like people assimilation of charity based on fiqh, miss target distribution, and public trust in zakat institution. This paper recommend a government, zakat management institution, and scholar to drive those incorporated significances as they actively encouraged each other.